HİND BİNT UTBE'NİN HAYATI VE KİŞİLİĞİ - SÜSLÜ, ZEYNEP (Fırat Üniveristesi, 2018)
İnsanoğlunun varlık serüveninde erkek; ilk insandan bu yana her dönemde kadına göre daha üstün sayılmıştır. Bu üstünlük, Allah Teâlâ'nın hidayet kaynağı olarak gönderdiği İslâm'la ortadan kaldırılmıştır. İslâm'ın, kadın konusundaki bu değişimini en çarpıcı şekilde örneklendiren Hind bint Utbe'yi tez çalışmamızda işlemenin uygun olacağını düşündük. Tezimizin giriş bölümünde; Arap toplumunun özelliklerinden, kadının genel durumundan, câhiliyye döneminden ve bu dönemde kadın, aile, evlilik müessesesi ve çocuklara toplumun bakış açısından, Kur'ân-ı Kerim'in câhiliyye değerlendirmelerinden bahsettik. Birinci bölümünde; Hind bint Utbe'nin Nesebi, Kabilesi, Emevi ve Haşimi çekişmelerine yer verdik. İkinci bölümde; Hind bint Utbe'nin doğumu, ailesi, evlilikleri ve çocukları hakkında bilgi vermeye çalıştık. Ayrıca son bölüm olan üçüncü bölümde ise; Hind bint Utbe'nin İslâm'la şereflenmesiyle, Hz. Peygamber'in vefatından önce ve sonraki dönemlerdeki durumundan, ayrıca şahsiyetinden de bahsederek tezimizi sonlandırdık.

In the struggle of humankind for existence, the man as a gender has always been considered superior to the woman as a gender since the first man on earth. This superiority has been eliminated for good with the religion of Islam, sent by Allah as a source of entering the right way. We thought that, in our study, it would be appropriate to study Hint bint Utbe, who exemplified the transformation concerning women most strikingly. In the introduction section of our thesis, we mentioned the characteristics of Arabian society, the general condition of women, the period of ignorance and the evaluation of the period of ignorance in the Koran Karim from the perspective of women, family, and the institution of marriage and the attitude of the society two words children. In the first section, we attempted to give an account of the familial origin of Hint bint Utbe end the contentions between the Umayyad and Hashemi tribes. In the section, we tried to give information about the birth of Hint bint Utbe, her family, her marriages and her children. In the last section, which is the third section, we aimed to finalize our thesis by referring to her becoming honored with Islam and to her state before and after the death of Prophet Muhammad as well as to her personality.
The life and personality of Hind Bint Utbe
Keywords: Din